2021
DOI: 10.1038/s41598-021-83542-0
|View full text |Cite|
|
Sign up to set email alerts
|

Dynamic and history of methane seepage in the SW Barents Sea: new insights from Leirdjupet Fault Complex

Abstract: Methane emissions from Arctic continental margins are increasing due to the negative effect of global warming on ice sheet and permafrost stability, but dynamics and timescales of seafloor seepage still remain poorly constrained. Here, we examine sediment cores collected from an active seepage area located between 295 and 353 m water depth in the SW Barents Sea, at Leirdjupet Fault Complex. The geochemical composition of hydrocarbon gas in the sediment indicates a mixture of microbial and thermogenic gas, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
29
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(30 citation statements)
references
References 80 publications
1
29
0
Order By: Relevance
“…Such conditions have been reported from many modern cold seeps from gas hydrate bearing areas, e.g. Cascadia Margin (Bohrmann et al, 1998(Bohrmann et al, , 2002Greinert et al, 2013), Gulf of Cadiz (Magalhães et al, 2012), Gulf of Mexico (Roberts and Feng, 2013), Congo Fan (Feng et al, 2010a), Barents Sea (Crémière et al, 2016;Argentino et al, 2021;Yao et al, 2021); the δ 18 O proxy has been applied to fossil seep carbonates as well (Pierre and Rouchy, 2004;Campbell, 2006;Campbell et al, 2008;Argentino et al, 2019;Bojanowski et al, 2021). Owing to their microbial origin, seep carbonates incorporate and harbor typical communities of methane-oxidizing archaea and sulfate-reducing bacteria (Marlow et al, 2014).…”
Section: Introductionmentioning
confidence: 64%
“…Such conditions have been reported from many modern cold seeps from gas hydrate bearing areas, e.g. Cascadia Margin (Bohrmann et al, 1998(Bohrmann et al, , 2002Greinert et al, 2013), Gulf of Cadiz (Magalhães et al, 2012), Gulf of Mexico (Roberts and Feng, 2013), Congo Fan (Feng et al, 2010a), Barents Sea (Crémière et al, 2016;Argentino et al, 2021;Yao et al, 2021); the δ 18 O proxy has been applied to fossil seep carbonates as well (Pierre and Rouchy, 2004;Campbell, 2006;Campbell et al, 2008;Argentino et al, 2019;Bojanowski et al, 2021). Owing to their microbial origin, seep carbonates incorporate and harbor typical communities of methane-oxidizing archaea and sulfate-reducing bacteria (Marlow et al, 2014).…”
Section: Introductionmentioning
confidence: 64%
“…On the contrary, the rates of microbial biogeochemical processes increases manifold in sediments in sites of methane release such as mud volcanoes and methane seeps. The composition of microbial communities of sediments in places where methane is released to the seafloor is also very different from background areas [21][22][23][24]. Our results show that methane concentrations and rates of microbial processes in sediments in the northern part of the Barents Sea were noticeably higher than in oligotrophic areas of the Laptev Sea, but they were orders of magnitude lower than in the methane seep areas in the Laptev Sea and in the Haakon Mosby Mud Volcano zone (Table 4).…”
Section: Microbial Processes Of Transformation Of Organic Matter In Sediments Of the Arctic Seas: The Role Of Methanementioning
confidence: 55%
“…The study of the processes of the methane cycle carried out under strictly anoxic (methanogenesis and anaerobic oxidation of methane) and under oxic (aerobic oxidation of methane) conditions, as well as the study of microbial processes at the border of oxic and anoxic zones of sediments in the Barents Sea provide new insights into the methane cycle in marine sediments. Most of studies dedicated to the methane cycling in the Barents Sea were focused on methane-rich sites, such as methane seeps and mud volcanoes [20][21][22][23]. Particularly, analysis of microbial processes at the Haakon Mosby Mud Volcano revealed that the high methane availability and different fluid flow regimens provide distinct niches for aerobic (Methylobacter and Methylophaga) and anaerobic (mostly ANME-3 lineage) methanotrophs [22].…”
Section: Introductionmentioning
confidence: 99%
“…Stable isotopes of C and O, petrography, and the mineralogy of methane-derived authigenic carbonates (MDAC) in the Arctic seas have been examined in several studies (Pauly, 1963;Schubert et al, 1997;Lein et al, 1999;Kravchishina et al, 2017;Savvichev et al, 2018a, etc.). MDAC were found as Mg-calcite cement and pavement-forming crusts at the sediment-water interface of various high latitudinal seas, such as in the North Sea at depths of 120-300 m (Crémière et al, 2016b;Mazzini et al, 2016), in the Norwegian Sea at 220 m (Sauer et al, 2017), and in the Barents Sea at 220-400 m (Crémière et al, 2016a;Hong et al, 2017;Argentino et al, 2021). They were also observed in other climatic zones, such as the Green Canyon in the northern Gulf of Mexico (Bian et al, 2013).…”
Section: Introductionmentioning
confidence: 94%